Desenvolvimento do extrato seco de Libidibia ferrea (jucá) como alimento funcional: caracterização química e avaliação das atividades antioxidante e anti-inflamatória em modelo de neuroinflamação - Chagas Neto, Francisco Cirineu (2018)
Caesalpinia ferrea, recently reclassified as Libidibia ferrea L.P. Queiroz, is a tree belonging to the Fabaceae family, traditionally used in the treatment of diabetes and gastrointestinal disorders. In the present study, the extraction of phenolic compounds obtained from L. ferrea leaves was optimized using a factorial design 23, in which was investigated the effects of the solvent concentration (methanol in water (v/v)), the proportion of L. ferrea leaves in solvent (w/v) and homogenization time (min) in ultra-turrax®. The extract with a higher phenol content was freeze-dried and chemically characterized (HPLC and NMR), in addition to the total phenol content and flavonoids content of the lyophilized. It was investigated the nutritional characteristics through the crude protein content and quantification of minerals, antioxidant properties (DPPH (2,2-diphenyl-1-picrylhydrazyl)) and anti-inflammatory potencies, evaluating the effect of the extract on the increased nitrite concentration in LPS-induced microbial culture. The optimization suggested that the extraction with 40% of methanol during 4 minutes of homogenization, using 24% of dry leaves (w/v) had the highest total phenol content (283.7 mgGAE/g). In the freeze-dried extract, the total phenol content (260 mgGAE/g) and total flavonoids (21.1 mgQE / g) were quantified, which are related to the presence of gallic acid, quercetin-3-O-glycoside and campferol-3-O glycoside in the plant determined by HPLC and NMR. The dry extract was non-cytotoxic, presenting 4.19% crude protein and high mineral content, such as Fe (21.65 mg/100 g dry extract), Mn (4.38 mg/100 g dry extract) and Zn (31.52 mg/100g dry extract). The extract showed antioxidative / sequestering activity of the DPPH radical, with an IC50 of 10.5 ± 1.01 μg/mL and anti-inflammatory activity (extract: 50 μg / mL), significantly reducing nitrite production in BV2 microglial cells. In view of the results obtained the standardized dry extract of L. ferrea showed interesting nutritional and potential antioxidant and anti-inflammatory characteristics, making the L. ferrea a potential source to a functional food.